Introducing information technology into the home: conducting a home assessment. - Zayas-Cabán, Teresa (American Medical Informatics Association, 2002)
Abstract As the home becomes an increasingly important site for health care, an increasing number of technology applications or devices are being introduced to support health at home. However, introducing new technology into a household raises a number of issues that must be considered prior to, during, and after the technology is implemented. This paper reviews the experiences of the UW-Madison Advanced Technologies for Health@Home Project, summarizing our assessment of household requirements that should be analyzed prior to introducing new technology. The overall goal of the Health@Home project is to improve the functionality and content of information technology innovations for the home. Using Venkatesh and Mazumdar's framework this article will summarize the relevant social, behavioral, technological, and physical dimensions of households that must be carefully assessed and understood to help ensure that the technology fits the needs of home residents.